2019
DOI: 10.1097/md.0000000000018067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of denosumab, a human monoclonal antibody of receptor activator of nuclear factor kappa-B ligand (RANKL), upon glycemic and metabolic parameters

Abstract: Osteoporosis is a complication of type 2 diabetes mellitus (T2DM). Blockade of receptor activator of nuclear factor kappa-B ligand (RANKL) improves osteoporosis, but might also improve glucose tolerance through reduction of hepatic insulin resistance. However, the effect of denosumab (a human monoclonal antibody of RANKL) upon glycemic and metabolic parameters is controversial. We revealed the effect of denosumab upon glycemic and metabolic parameters for 52 weeks. We evaluated 20 individuals diagnosed with bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
0
14
0
2
Order By: Relevance
“…Schwartz et al [ 28 ] did not detect any significant effect of Dmab on metabolic parameters of osteoporotic women enrolled in the FREEDOM study, while in a further post hoc analysis of the same trial, Napoli et al [ 29 ] found that treatment with Dmab was associated with a reduction of FPG in drug-free diabetic women. More recently, Abe et al [ 30 ] reported a positive effect of one-year Dmab treatment on insulin resistance and HbA1c in a cohort of osteoporotic patients affected by T2DM. These observations suggest that RANKL blockade may be clinically relevant in the presence of abnormalities of glucose homeostasis, as suggested by previous animal and clinical studies [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schwartz et al [ 28 ] did not detect any significant effect of Dmab on metabolic parameters of osteoporotic women enrolled in the FREEDOM study, while in a further post hoc analysis of the same trial, Napoli et al [ 29 ] found that treatment with Dmab was associated with a reduction of FPG in drug-free diabetic women. More recently, Abe et al [ 30 ] reported a positive effect of one-year Dmab treatment on insulin resistance and HbA1c in a cohort of osteoporotic patients affected by T2DM. These observations suggest that RANKL blockade may be clinically relevant in the presence of abnormalities of glucose homeostasis, as suggested by previous animal and clinical studies [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, in a further post hoc analysis considering diabetic patients [ 29 ], treatment with Dmab was associated with a significant reduction in FPG in antihyperglicemic drug-free diabetic women. Abe et al [ 30 ] recently reported a reduction of HbA1c levels in a cohort of osteoporotic patients with T2DM after one year of Dmab treatment, strengthening the hypothesis that the impact of RANKL blockade may be more relevant in presence of overt abnormalities of glucose homeostasis.…”
Section: Introductionmentioning
confidence: 91%
“…However, multiple studies, randomized controlled trials and observational studies, have assessed the effect of Denosumab on insulin sensitivity and FPG with contradictory results. In a few studies, the authors demonstrate a beneficial effect, in which Denosumab decreased FPG [4,19]; however, Schwartz et al demonstrate that Denosumab clearly increased FPG [20]. To address this conflict, a systematic review was conducted, aimed to evaluate the effects of Denosumab on different glycemic parameters.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…M. Rubin et al собираются определить, как применение антител к RANKL в течение 1 года повлияет на МПК, микроархитектонику, качество костного матрикса и количество AGEs в его составе [24]. Некоторые исследователи также отмечают положительное влияние деносумаба на гликемический контроль у пациентов с СД 2-го типа и ОП [25,26]. Точные механизмы этого эффекта пока не выяснены, но предполагается, что антитела к RANKL способны снижать печеночную инсулинорезистентность [26].…”
Section: Comorbid Conditionsunclassified
“…Некоторые исследователи также отмечают положительное влияние деносумаба на гликемический контроль у пациентов с СД 2-го типа и ОП [25,26]. Точные механизмы этого эффекта пока не выяснены, но предполагается, что антитела к RANKL способны снижать печеночную инсулинорезистентность [26]. Влияние деносумаба на гликемию и другие метаболические параметры у пациентов с СД 2-го типа на сегодняшний день остаются спорным вопросом, который требует проведения дальнейших исследований.…”
Section: Comorbid Conditionsunclassified